Cardiac remodeling in a fetal growth restriction cohort – a follow-up study from preadolescence into adolescence. (25th November 2020) - Fabijanovic, D; Loncaric, F; Sarvari, S; Vellve, K; Rodriguez-Lopez, M; Sepulveda-Martinez, A; Blanco, I; Cikes, M; Sitges, M; Gratacos, E; Bijnens, B; Crispi, F
Abstract: Background and aim: The persistence of cardiovascular changes in fetal growth restriction (FGR) has been demonstrated from prenatal to preadolescent age, supporting the hypothesis of primary cardiac programming in FGR and the association between low birth weight and cardiovascular risk in adulthood. The aim was to follow-up the FGR cohort and explore the cardiac function and shape in adolescence. Methods: FGR was defined by estimated fetal weight and birth weight below the 10th centile, while the control group consisted of normally grown fetuses with birth weight above the 10thcentile. The patients were followed from preadolescence (8–12 years of age) to adolescence (12–17 years of age) with 2-D echocardiography and deformation imaging. The adolescent participants underwent a cardiopulmonary exercise test, where echocardiography was performed at peak exercise. Sphericity index was calculated as the ratio of the LV apex-to-base length and LV basal diameter, measured in 4-chambre view. Results: The cohort included 56 participants: individuals with FGR (n=22) and controls (n=34). The mean follow-up was 4.4±0.5 years. The preadolescent FGR cohort was younger (10 vs. 11 years, p=0.004), of shorter height, and lower body weight. In FGR, the trend in smaller LV end-diastolic volumes (LVEDV) was paired with a shorter apex-to-base length (63 vs. 68 mm, p=0.006), and a significantly more spherical LV (1.9 vs 2.0, p=0.004). While the LV ejection fraction was preserved, the LV global longitudinal strain (GLS) was reduced (21.21 vs 22.45%, p=0.001) and the relaxation time impaired. In the follow-up adolescent cohort, there were no differences in height, weight, LV dimensions, LV sphericity, LV GLS or relaxation time. During the follow-up period, the FGR cohort had a significantly higher increase in weight (40 vs. 31%, p=0.016) and BMI (18 vs. 11%, p=0.008). The same was seen in cardiac dimensions, showing a higher increase in LVEDV (35 vs. 27%, p=0.049) and the LV base-to-apex length (24 vs. 17%, p<0.001) (Figure 1); but equal increase of the LV basal diameter (p=0.770), resulting in a difference in the change of LV sphericity (0 vs. −13%, p=0.007) between subgroups. The rise in LVGLS was also higher in the FGR cohort (6 vs. 1%, p=0.049). During the exercise test there was no difference in maximal workload (112.5 vs. 125 Watts, p=0.981) or oxygen consumption (28.8 vs. 29.1 mL/min/kg, p=0.076). At peak exercise no differences were seen in cardiac dimensions, LV diastolic or systolic function. Conclusion: The results suggest changes in cardiac shape and function, described in individuals with FGR in prenatal and preadolescent age, seem to be ameliorated in adolescence related to compensatory growth as compared to healthy controls. These findings offer novel information in the research of elevated cardiovascular risk in adults with FGR. Funding Acknowledgement: Type of funding source: None